Pengaruh Pengaruh Model Pembelajaran Problem Based Learning (PBL) Terhadap Minat dan Hasil Belajar Siswa Pada Materi Larutan Penyangga Kelas XI di MAN 5 Kediri - Indasari, Caressa; Amirul Mu’minin, Ali (Jurnal Riset Pendidikan Kimia (JRPK), 2024)
This purpose of this study is to describe the effect of the Problem Based Learning (PBL) learning model on students learning interest in class XI buffer solution material at MAN 5 Kediri, to describe the effect of the Problem Based Learning (PBL) learning model on student learning outcomes in class XI buffer solution material at MAN 5 Kediri, and to describe the effect of the Problem Based Learning (PBL) learning model on student interest and learning outcomes in class XI buffer solution material at MAN 5 Kediri. The sample for this research was 33 students of class XI MIPA 1 and 35 students of XI MIPA 2 at MAN 5 Kediri. This research data collection technique uses a questionnaire method to obtain learning interest data and a test method to obtain learning outcome data. The data analysis technique used is statistical parameter data analysis using the Independent Sample T-Test and MANOVA test. The results of this research show that there is an effect of the Problem Based Learning (PBL) learning model on students learning interest in the buffer solution material for class XI at MAN 5 Kediri as evidenced by the average posttest interest in learning class XI MIPA 1 is greater than that of class XI MIPA 2, namely 139,82 ≥ 129,23 and the value of Sig. (2-tailed) experimental group, namely 0,000 ≤ 0,05, so that H0 is rejected and Ha is accepted, there is an effect of the Problem Based Learning (PBL) learning model on student learning outcomes in class XI buffer solution material at MAN 5 Kediri as evidenced by the average posttest learning outcomes for class XI MIPA 1 is higher than class XI MIPA 2, namely 81,21 ≥ 68,29 and the value of Sig. (2-tailed) experimental group that is 0,000 ≤ 0,05, so that H0 is rejected and Ha is accepted, there is an influence of the Problem Based Learning (PBL) learning model on student interest and learning outcomes in class XI buffer solution material at MAN 5 Kediri as evidenced by the significance value of interest and learning outcomes being 0,000. The significance value show 0,000 ≤ 0,05, so H0 is rejected and Ha is accepted.